Development of the Professional Experience Model in Educational Administration on Digital Age: การพัฒนารูปแบบการฝึกประสบการณ์วิชาชีพบริหารการศึกษาในยุคดิจิทัล - Jankaew, Wimol (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This research article were: 1) to study the current and desirable states of the Professional Experience Model in Educational Administration on Digital Age ; and 2) to develop of the Professional Experience Model in Educational Administration on Digital Age. Using mixed - methods research approach that consisted of 4 steps as follows: (1) study of 90 University; (2) construction of a model; and (3) verification of the model by 30 experts, and an evaluation of the model by a focus group of 15 experts, followed by final adjustments to the model. The research instruments were a questionnaire and an evaluation form. The data were analyzed by content analysis and descriptive statistics. The research results were as follows : 1) The overall of current and desirable states of the Professional Experience Model in Educational Administration on Digital Age at high level and at the highest level respectively 2) The model was composed of 3 parts : The 1st part was that the principle and objective model. The second part was the factor of model, which consisted of 4 factors, They were professional standard, professional experience criteria, learning outcome and competency and usage digital for supervision. The third part was an implementation